Preferensi Pemilihan Perumahan Di Pinggiran Kota Surakarta Berdasarkan Motivasi Pembelian Rumah - Nugroho, Sigit; Djunaedi, Achmad; Iskandar, Doddy Aditya (Jurnal Tata Kota dan Daerah, 2018)
Rapid population growth in Surakarta requires the need for land for housing. Due to limited land available, the fulfillment of housing needs spread to the suburbs around the city of Surakarta. In choosing a home, whether it be consumption or investment, the convenience of individuals or households will have different preferences depending on the characteristics. The purpose of this study is to determine the preferences of housing selection based on the motivation of home purchase and to know the relationship of household characteristics with motivation of home purchase. The method used is quantitative descriptive method with percentage tendency and mean analysis to know housing selection preferences and cross tabulation analysis and Chi-Square test to know the relation between household characteristics and motivation of home purchase. The result of the analysis of housing preferences is, in households that buy houses for consumption, the main preference in housing selection is: 1) the physical condition of the environment (2.84); 2) home financing (2.76); and 3) location and accessibility (2.76). While in households that have motivations for investment, the main preference in housing selection is: 1) the physical condition of the house (2.83); 2) location and accessibility (2.80); and 3) the physical condition of the environment (2.78). Characteristics of households that influence the motivation of home purchase is the level of education (sig. 0.000); households income level (sig 0.001) and housing type (sig 0.006. With the knowledge of housing selection preference based on purchasing motivation, it is hoped that it can be used as input in making policy for the government in housing development especially in fulfilling the needs of housing for the right target, especially for low income people who mostly still have difficulty access to own housing.Keywords: selection of housing, motivation of home purchase, sub-urban area